Generalized time limited Gramian based model reduction - Kumar, Deepak; Haja Mohideen, Ahmad Jazlan; Sreeram, Victor (IEEE, 2018)
In this article, a generalized time limited Gramian based model reduction method is presented for unstable systems. The proposed approach is also applicable to a system if it has eigenvalues with opposite polarities and equal magnitude. The standard time-limited Gramians are extended for unstable systems by transforming the original system into a new system which involves the solution of two Riccati equations. The proposed approach is also illustrated by a numerical example.